Cellulose extraction via acid digester and alkaline digester from empty fruit bunch (efb) and banana trunk - Surenthran, K Sundar (2014)
Cellulose usage is essential in various industries mainly in paper industry, food industry, pharmaceutical and paint industry. Cellulose is mainly obtained from wood but the source is very limited in developed countries which cause the industries to find an alternative resource. Agricultural residue is the unconventional resource that contains natural lignocellulosic materials that able to replace the dominant of wood. The main contents of lignocellulosic material are cellulose, hemicellulose and lignin. Lignocellulosic materials are renewable, largely unused, and easily available sources of material. Rice straw, orange peel and sugar beet pulp are a few examples of agricultural residue. In this study, the cellulose is being extracted from empty fruit bunch (EFB) and banana trunk. The cellulose yield obtained from both materials are compared. There are many approaches that have been studied in extraction of cellulose such as steam explosion, ionic liquid, liquid hot water treatment and many more. In current study, two different methods are being used in obtaining the cellulose that is acid digestion and alkaline digestion. Acid digester uses sulphuric acid, ethylenediaminetetraacetic (EDTA) acid and water in extraction cellulose. Meanwhile alkaline digester uses sodium hydroxide instead of sulphuric acid. The materials undergo three major steps before recovering the cellulose that is pulping process followed by filtration of pulp and finally, bleaching of the pulp recovered. The recovered cellulose are verified using fourier transform infrared (FTIR) and scanning electron microscopy (SEM) which is compared with a standard cellulose. Based on the results obtained alkaline digester have a higher yield of cellulose compared to acid digester by controlling other parameters. Meanwhile, banana trunk has a higher cellulose content compared to EFB for both acid and alkaline digesters respectively.